The influence of professional attitude, welfare, self-sustaining development, and job satisfaction on teacher performance - Tri Murwaningsih; Muna Fauziah (Journal of Education and Learning (EduLearn), 2023)
This study aims to identify: i) The effect of teacher welfare, self-sustaining development, job satisfaction, and teacher performance on the teaching professional attitude; ii) The effect of teacher welfare on self-development, job satisfaction, and teacher performance; iii) The effect of self-sustaining development on the professional attitude, welfare, job satisfaction, and teacher performance of teachers; and iv) The effect of teacher job satisfaction on teaching performance. This study was quantitative research with a correlational type. The sample was 155 vocational high school teachers in Central Java, Indonesia. Data was collected through a questionnaire technique. The data analysis technique used structural equation modeling with the linear structural relationship type. The study revealed that the teacher's professional attitude has an effect on teacher welfare but not on self-development, job satisfaction, or teacher performance. Teacher welfare has an effect on independent development but has no effect on teacher performance. Hence, independent development does not affect job satisfaction but affects teacher performance. Furthermore, job satisfaction has no effect on teacher performance. These findings can be used as study material for future researchers to analyze the research variables or other variables, such as leadership style, work motivation, work discipline, and others.